2021
DOI: 10.1146/annurev-pharmtox-030920-011143
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Tuberculosis Drugs: Translation to Regimen Composition for Drug-Sensitive and Multidrug-Resistant Tuberculosis

Abstract: Tuberculosis (TB) kills more people than any other infectious disease. Challenges for developing better treatments include the complex pathology due to within-host immune dynamics, interpatient variability in disease severity and drug pharmacokinetics-pharmacodynamics (PK-PD), and the growing emergence of resistance. Model-informed drug development using quantitative and translational pharmacology has become increasingly recognized as a method capable of drug prioritization and regimen optimization to efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 146 publications
(175 reference statements)
0
39
0
Order By: Relevance
“…We hope that these efforts will facilitate the support of further studies on translational approaches and their implementation in other infectious diseases. In fact, the value of model‐based translation for both antituberculosis and antimalarial treatments have recently been highlighted 81,82 . Of note, the threat of accelerating anti‐infective drug resistance has not reduced during the SARS‐CoV‐2 pandemic.…”
Section: Translation In the New Eramentioning
confidence: 99%
See 1 more Smart Citation
“…We hope that these efforts will facilitate the support of further studies on translational approaches and their implementation in other infectious diseases. In fact, the value of model‐based translation for both antituberculosis and antimalarial treatments have recently been highlighted 81,82 . Of note, the threat of accelerating anti‐infective drug resistance has not reduced during the SARS‐CoV‐2 pandemic.…”
Section: Translation In the New Eramentioning
confidence: 99%
“…In fact, the value of model-based translation for both antituberculosis and antimalarial treatments have recently been highlighted. 81,82 Of note, the threat of accelerating antiinfective drug resistance has not reduced during the SARS-CoV-2 pandemic.…”
Section: Translation In the New Eramentioning
confidence: 99%
“…A clinical trial of rifapentine‐containing TB treatment‐shortening regimens (Study 31) investigated a 4‐month regimen that achieved noninferiority compared with the 6‐month standard‐of‐care regimen. MIDD played a pivotal role in the success of this trial 170–173 . First, a direct comparison in the chronic mouse model showed that the standard rifapentine dose (10 mg/kg) was superior to the standard rifampicin dose (10 mg/kg) in the mouse; however, this finding did not translate well to the earlier phase IIB study (Study 29 (https://clinicaltrials.gov/ct2/show/NCT00694629)), which evaluated rifapentine substitution for rifampin at this dose.…”
Section: Global Healthmentioning
confidence: 98%
“…MIDD played a pivotal role in the success of this trial. [170][171][172][173] First, a direct comparison in the chronic mouse model showed that the standard rifapentine dose (10 mg/kg) was superior to the standard rifampicin dose (10 mg/kg) in the mouse; however, this finding did not translate well to the earlier phase IIB study (Study 29 (https://clini caltr ials.gov/ct2/show/NCT00 694629)), which evaluated rifapentine substitution for rifampin at this dose. Therefore, the choice of an optimal rifapentine dose was based on clinical PK/PD work from a separate dose-ranging study.…”
Section: Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation